STANOWISKO EUROPEJSKIEGO TRYBUNAŁU SPRAWIEDLIWOŚCI W SPRAWIE PRZEPISÓW O NIEDOSTATECZNEJ KAPITALIZACJI - Sobiech, Agnieszka (Wydział Prawa i Administracji UAM, 2004)
On December 12, 2002 the European Court of Justice delivered a verdict in Lankhorst-Hohorst GmbH case (Case C-324/00). The ECJ held that the German thin capitalization rules are incompatible with the freedom of establishment principle provided for in the founding treaty of the European Community. The Lankhorst-Hohorst case revolved around tax ramifications of the interest that a German company was paying as a consequence of a loan incurred from its Dutch parent company. The ECJ claims that the freedom of establishment, set out in clause 43 of the EC Treaty is infringed upon if a German subsidiary of a non-German parent company is taxed more than it would be i f the parent company was German. The ECJ rejects all arguments supporting the German thin capitalization rules, including those regarding fiscal cohesion of the income tax system, reduction in tax revenue, risk of tax evasion ad efficiency of fiscal supervision. The ECJ’s decision may have serious implications for several countries in the European Union and EU applicant countries because these rules may now be challenged insofar as they are based on the distinction between domestic and cross-border cases.
THE POSITION OF THE EUROPEAN COURT OF JUSTICE ON UNDERCAPITALIZATION REGULATIONS